Etika Bisnis Islam dalam Perilaku Blantik di Pasar Hewan Jetis Ponorogo - Pancawati, Lilin; Purbasari , Verbena Ayuningsih (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Jetis Animal Market in Ponorogo is one of the largest traditional economic centers in the former Madiun Residency that continues to maintain a trading system involving intermediaries known as blantik. In practice, the behavior of blantik does not always fully reflect the values of Islamic business ethics, such as honesty, justice, responsibility, trustworthiness (amanah), and the prohibition of riba and gharar. Practices such as concealing the actual condition of animals and engaging in price mark-ups indicate the importance of conducting an in-depth study of Islamic business ethics within traditional market transactions. This study employed a qualitative field research approach. Data were collected through in-depth interviews with six blantik operating in the Jetis Animal Market. The data were analyzed using the interactive model of Miles and Huberman, which includes data collection, reduction, presentation, and conclusion drawing. Data validity was ensured through member checking. The findings show that most blantik have an adequate understanding of Islamic business ethics; however, their implementation tends to be situational and influenced by surrounding conditions. Principles of honesty and amanah are sometimes compromised to avoid financial losses, although honesty, justice, trustworthiness, and responsibility remain the main ethical guidelines in their business practices. Elements of riba are rarely found because transactions are conducted in cash, while gharar is minimal due to direct visual and physical access to the animals being traded. Economic pressure, price fluctuations, and market competition significantly affect ethical behavior, while social environment, market traditions, regulatory oversight, and the level of religious understanding also play important roles in shaping ethical consistency among blantik.